Vincent van Gogh und die Moderne : 1890-1914. - Költzsch, Georg-W.; de Leeuw, Ronald (Freren : Luca Verlag, 1990)
Amiet, Cuno ; Beckmann, Max ; Bernard, Emile ; Bevan, Robert ; Boch, Anna ; Braque, Georges ; Camoin, Charles ; Delaunay, Robert ; Derain, André ; Dix, Otto ; Dufy, Raoul ; Ernst, Max ; Friesz, Othon ; Gauguin, Paul ; Gerstl, Richard ; Gestel, Leo ; Heckel, Erich ; Jawlensky, Alexej ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Klimt, Gustav ; Kokoschka, Oskar ; Macke, August ; Marc, Franz ; Marquet, Albert ; Matisse, Henri ; Meidner, Ludwig ; Miró, Joan ; Modersohn-Becker, Paula ; Mondriaan, Piet ; Monet, Claude ; Morgner, Wilhelm ; Münter, Gabriele ; Munch, Edvard ; Nauen, Heinrich ; Nolde, Emil ; O'Conor, Roderic ; Pechstein, Max ; Picasso, Pablo ; Robertson, Suze ; Rohlfs, Christian ; Schiele, Egon ; Schmidt-Rottluff, Karl ; Séguin, Armand ; Signac, Paul ; Sluyters, Jan ; Soutine, Chaim ; Prikker, Johan Thorn ; Toorop, Jan ; Valtat, Louis ; van de Velde, Henry ; van Dongen, Kees ; de Vlaminck, Maurice
van Gogh und die Moderne, Museum Folkwang, Essen, 11. August 1990 - 4. November 1990 ; Van Gogh Museum, Amsterdam, 16. November 1990 - 18. Februar 1991
boek
Keywords: van Gogh, Vincent